Analysis on the local heavy rainfall caused by cold front in midsummer - Yinghua WEI; Hong CHEN; Yiwei LIU; Xiaomeng LIN (暴雨灾害, 2021)
Using conventional observations,wind profiling radar and the retrieval data from Variational Doppler Radar Analysis System (VDRAS),we analyzed the atmospheric circulation,thermo-dynamic structural characteristics and rainstorm triggering mechanism,and discussed the causes of a local heavy rainfall event in North China occurred behind a cold front on 21 July 2017. The results showed that the torrential rainfall occurred under the weather conditions where the subtropical high at 500 hPa was lifted northward and the return cold air in the low-level invaded. The shear line at 850 hPa was the main large-scale influencing system. The torrential rainfall was located on the cold air side about 300 km behind the surface cold front. Under the control of cold air returning in boundary layer,the atmosphere below 850 hPa presented as a stable stratification of γ < γs. At the same time,due to the influence of the subtropical high northward,the instability of the 700-500 hPa stratum was strengthened,so the unstable atmosphere was situated over the stable cold layer,which contributed to the favorable environmental conditions for "elevated convection". Corresponding to the sinking movement of the low-level cold air,the rising motion of warm and humid air was above the cold layer,and the meso-scale convergence line near the 1.4 km height played an important role in triggering the elevated convection. We further found that the belt-shaped meso-scale convective system moved slowly to the east,and it had obvious characteristics of back-propagation and train effect,which was the main reason for the long duration of the heavy rainfall.